Pentoxifylline prevents indomethacin induced acute gastric mucosal damage in rats: role of tumour necrosis factor alpha. Issue 7 (July 1994) - Santucci, L; Fiorucci, S; Giansanti, M; Brunori, P M; Di Matteo, F M; Morelli, A
Abstract : Neutrophil adherence within the gastric microcirculation is thought to be a major step in the pathogenesis of gastric mucosal damage induced by indomethacin. Pentoxifylline, a methylxanthine derivative, prevents leukocyte adherence to vascular endothelium and protects organs from shock by reducing tumour necrosis factor alpha (TNF alpha) concentrations. Rats were treated with 20 mg/kg oral indomethacin, pretreated with vehicle or with four different doses of pentoxifylline intraperitoneally, and killed after three hours. The gross gastric mucosal injury, neutrophil margination into the gastric microcirculation, mucosal concentrations of 6-keto-prostaglandin F1 alpha (PGF1 alpha), and PGE2 and serum TNF alpha values were measured. Whether the pentoxifylline induced protection involved nitric oxide mediated pathways or gastric acid secretion was evaluated. The data indicate that pentoxifylline reduces indomethacin induced mucosal damage and neutrophil margination in a dose dependent manner without exerting any effect on gastric mucosal prostaglandin concentrations. The maximally effective dose (200 mg/kg) of pentoxifylline reduced gastric damage by 90% and slightly stimulated acid secretion. The effect of pentoxifylline was not affected by pretreatment with the nitric oxide inhibitor. Pentoxifylline prevented the indomethacin induced increase in TNF alpha concentrations in a dose dependent fashion. Serum TNF alpha values were 30.5 (7.0) IU/ml (mean (SEM)) in rats treated with indomethacin alone and 5.0 (2.5) IU/ml (p < 0.01) in rats treated with indomethacin plus 200 mg/kg pentoxifylline. Pentoxifylline, therefore, prevents the acute gastric mucosal damage and neutrophil margination induced by indomethacin and reduces indomethacin induced release of TNF alpha.